STAND UP CATEGORY : STRATEGI PEMBELAJARAN AKTIF UNTUK MENINGKATKAN KETERAMPILAN BERBICARA (MAHARAT AL-KALAM) PADA MAHASISWA JURUSAN PENDIDIKAN BAHASA ARAB UIN SUNAN KALIJAGA YOGYAKARTA - ADZFAR AMMAR (Prosiding Konferensi Nasional Bahasa Arab, 2015)
This study aims to determine the implementation of the stand up category strategy in Arabic learning to improve speaking skills (maharat al-kalam) and to verify whether there is a significant difference from the study results of the subject al-istima 'wa al-kalam between the experimental group and control group in Arabic Education Department students at State Islamic University Sunan Kalijaga. Methods of data collection was conducted by using test, interview, observation and documentation. The study shows that from the result of statistical analysis known that posttest non Parametric test between the control group and the experimental obtained Sig value 0.002 <0.05 which means that there are significant differences in learning outcomes between the control and experimental groups. While the T test value of pretest and posttest experimental group produces Sig value 0.000 <0.05 which means that there is a significant increase in the experimental group students' learning outcomes. It can be concluded that the stand up category strategy can be used as an alternative solution in improving student learning outcomes in learning conversational skills (maharat al-kalam).Keywords: Stand up Category, Learning Strategies and Speaking Skills